2014
DOI: 10.1111/asj.12280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding polyphenol‐rich winery wastes on digestibility, nitrogen utilization, ruminal fermentation, antioxidant status and oxidative stress in wethers

Abstract: Four wethers were used in a 4 × 4 Latin square design experiment to evaluate the availability of two types of winery wastes, winery sediment and grape pomace, as ruminant feeds possessing antioxidant activities. Each wether was assigned to one of the following four treatments: (i) 75 g/kg winery sediment (WS) on a dry matter (DM) basis; (ii) 166 g/kg DM winery grape pomace (WP); (iii) control diet (CD; 17 g/kg DM soybean meal);and (iv) only tall fescue hay (TFH; no additive). Winery sediment and grape pomace h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…In contrast, Spanghero et al (2009) observed no difference between white and red varieties regarding ruminal degradability of GP and grape seeds. While for sheep the CP digestibility of dried GP from red compared with white varieties determined in our study are in a similar range as presented in the DLG feeding tables (DLG 1997), very different results regarding CP digestibility for sheep of dried GP were reported from others (Baumgärtel et al 2007;Ishida et al 2014).…”
Section: Nutrient Digestibility and Energy Content Of Dried And Ensilsupporting
confidence: 70%
See 1 more Smart Citation
“…In contrast, Spanghero et al (2009) observed no difference between white and red varieties regarding ruminal degradability of GP and grape seeds. While for sheep the CP digestibility of dried GP from red compared with white varieties determined in our study are in a similar range as presented in the DLG feeding tables (DLG 1997), very different results regarding CP digestibility for sheep of dried GP were reported from others (Baumgärtel et al 2007;Ishida et al 2014).…”
Section: Nutrient Digestibility and Energy Content Of Dried And Ensilsupporting
confidence: 70%
“…Data on this topic are very scare; only one study investigating the feed value for sheep of fresh GP from two different grape varieties originating from Germany is known (Baumgärtel et al 2007). Other published data on the feed value of dried or ensiled GP originate from non-EU countries, such as Iran (Pirmohammadi et al 2007(Pirmohammadi et al , 2012, Japan (Ishida et al 2014), Italy (Spanghero et al 2009) and Turkey (Basalan et al 2011). These data are not suitable to estimate the feed value of GP originating from Germany for ruminants with a sufficient correctness.…”
Section: Nutrient Digestibility and Energy Content Of Dried And Ensilmentioning
confidence: 99%
“…The positive effects of polyphenols on oxidative status were detected both in goats [115] and ewes [24]. The antioxidant effects, in vivo, are rather complex.…”
Section: Effect On Blood Metabolitesmentioning
confidence: 99%
“…For instance, GP increased the biodiversity degree of intestinal microflora in broiler chicks [13], and improved the gain-to-feed ratio and overall performance in pigs [14,15]. Further, GP altered the nitrogen metabolism and decreased the ruminal ammonia production in male sheep [16], was shown to modify the rumen microbial population involved in methane metabolism [17], enhance the growth of facultative probiotic bacteria and inhibit the growth of pathogenic ones in lambs [18], but had no effect on milk yield and composition of dairy ewes [19]. In dairy cows, few studies, with varying results, have investigated the effects of GP dietary inclusion on milk production, composition and total polyphenols content as well as on the overall performance of animals [10,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%